Preparation of Hotel Rooms for Euro-2012 in Ukraine Подготовка гостиничных номеров в Украине к Евро-2012 - Zima Aleksandr G.; Podgainaya Valentina A., (Problemi Ekonomiki, 2011)
In article the problem of preparation of hotel rooms in Ukraine to Euro-2012 is considered, existing problems and directions of their decision are defined. В статье рассматривается проблема подготовки гостиничных номеров в Украине к Евро-2012, определяются существующие проблемы и направления их разрешения.